2007
DOI: 10.1152/ajpcell.00343.2006
|View full text |Cite
|
Sign up to set email alerts
|

siRNA knock down of casein kinase 2 increases force and cross-bridge cycling rates in vascular smooth muscle

Abstract: Smolock EM, Wang T, Nolt JK, Moreland RS. siRNA knock down of casein kinase 2 increases force and cross-bridge cycling rates in vascular smooth muscle. Am J Physiol Cell Physiol 292: C876-C885, 2007. First published September 20, 2006; doi:10.1152/ajpcell.00343.2006.-Contraction of smooth muscle involves myosin light chain (MLC) kinase catalyzed phosphorylation of the regulatory MLC, activation of myosin, and the development of force. However, this cannot account for all aspects of a smooth muscle contraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 56 publications
2
19
0
Order By: Relevance
“…Calcium channel function in organ-cultured smooth muscle tissues and cell-cultured smooth muscle cells have been shown to significantly decrease as time in culture increases (20,26). However, consistent with previous studies from our laboratory using organ culture of vascular smooth muscle tissues (21,48,49), functional voltage-dependent calcium channels are retained. This is based on the observation that both vascular and BSM tissues subjected to organ culture exhibit rapid and robust contractions in response to KCl-PSS (21, 48, 49 and Figs.…”
Section: Quantification Of Rock-i and Pkg In Organ-cultured Bsm Tissuesupporting
confidence: 85%
See 3 more Smart Citations
“…Calcium channel function in organ-cultured smooth muscle tissues and cell-cultured smooth muscle cells have been shown to significantly decrease as time in culture increases (20,26). However, consistent with previous studies from our laboratory using organ culture of vascular smooth muscle tissues (21,48,49), functional voltage-dependent calcium channels are retained. This is based on the observation that both vascular and BSM tissues subjected to organ culture exhibit rapid and robust contractions in response to KCl-PSS (21, 48, 49 and Figs.…”
Section: Quantification Of Rock-i and Pkg In Organ-cultured Bsm Tissuesupporting
confidence: 85%
“…Myosin content, however, in the Hellstrand study (35) was decreased by 50%. This is consistent, in terms of force development, with our previous work showing that a vascular preparation could be subjected to organ culture for up to 9 days in a serum-free media (21,48,49). More recently, Corteling et al (16) again using a vascular preparation, showed no loss of contractility in response to UTP stimulation, no decrease in caldesmon content, but a 50% loss of calponin.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…RIP-2 phosphorylates p38 MAPK (22), so the inhibition of RIP-2 would simply inhibit p38 MAPK. Casein kinase-2 knockdown using short interfering RNA resulted in an increase in force responses in vascular smooth muscle (38), suggesting that a similar mechanism of force modulation may be present in the myocardium.…”
Section: Discussionmentioning
confidence: 98%